The genus Catathelasma (Catathelasmataceae, Basidiomycota) in China - Zai-Wei Ge; Jian-Yun Wu; Yan-Jia Hao; Qingying Zhang; Yi-Feng An; Martin Ryberg (MycoKeys, 2020)
Two new species, Catathelasma laorentou and C. subalpinum, are described on the basis of morphological characters, phylogenetic evidence, host preferences and geographic distributions. A taxonomic key to the known species in China is also provided to facilitate identification. Based on samples from temperate Asia, Europe and North America, the phylogeny of Catathelasma was reconstructed using the internal transcribed spacer (ITS) region, the large subunit (LSU) of the ribosomal DNA and the translation elongation factor 1-α (TEF1).The phylogenetic results showed that Catathelasma contains two monophyletic clades: the /subalpinum clade and the /imperiale clade. The Asian species C. laorentou and C. subalpinum are closely related to the North American C. sp. (labelled as C. ventricosum in GenBank) in the /subalpinum clade, whereas C. imperiale and C. singeri are closely related in the /imperiale clade.